NEW DATA ON COMPARATIVE ANALYSIS OF NOCTUID MOTHS (LEPIDOPTERA, NOCTUIDAE) OF THE ISLANDS TULENEI, CHECHEN AND NORDOVIY OF THE NORTH-WESTERN CASPIAN SEA - G. M. Abdurakhmanov; A. G Abdurakhmanov; N. S. Kurbanova; N. M. Melikova (Юг России: экология, развитие, 2014)
The work gives the species composition and geographical distribution of the noctuid moths (Lepidoptera,Noctuidae) of the islands Tulenei, Chechen and Nordoviy of the north-western Caspian sea. Provides a list of common species of moths for all three of the Islands, as well as the list of rare with small populations of species.